Optical studies of topological insulator Bi1:5 Sb0:5 Te1:8 Se1:2 using terahertz time-domain spectroscopy. - Tang, Chi Sin. (2012)
Topological insulators are insulating materials with conducting surface states and insulating bulk states. Their surface states are topologically protected, meaning that unlike ordinary surface states, they cannot be destroyed by impurities and imperfections. This property is attributed to the presence of time-reversal symmetry and spin-orbit interaction, which occurs in heavy elements such as mercury and bismuth. Topological insulators